3*-7/3(3*-7/3+14)=

Simple and best practice solution for 3*-7/3(3*-7/3+14)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*-7/3(3*-7/3+14)= equation:


3*-7/3(3*-7/3+14)=0

We simplify the equation to the form, which is simple to understand
3*-7/3(3*-7/3+14)=0

Simplifying:
+21/3*(3*-7/3+14)=0

Simplifying:
+21/3*(+21/3+14)=0

Simplifying:
+7*(+21/3+14)=0

Simplifying:
+7*(+7+14)=0

Simplifying terms in parentheses
+7*(+7)=0

Reorder the terms in parentheses
+(+49)=0

Remove unnecessary parentheses
+49=0

We move all terms containing to the left and all other terms to the right.
0=0-49

We simplify left and right side of the equation.
0=-49

0=-49

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 10x-18x-24=5[2x+3x+4-22] | | 14x-15=62x-5 | | 8+3x-15=23 | | W+3=1w+6 | | 3(x+5)+1=19 | | 42*-7/3= | | 13-4x=1-n | | 1x+(2x+3)=15 | | 3t^2=24t | | 9*-7/1= | | -20=4(x+4) | | 5x=-3+6x | | 2z-31=2f-11 | | 5x-6x=-3x+6x-6x | | 4(3+-6a)=36a | | 22k=154 | | -4x-48=5(2x-4) | | 8g-10-2g=-6g+10+9g | | 5x+3=33+2x | | .8h-9=4 | | 5y+1=2y-2 | | 12x=380 | | 5y+17=2y-2 | | 2x+4y=380 | | 8(2+h)=2(5+h) | | 5[4x-3(x+7)]=8x-3 | | 2(y+4)+3(y+3)=(y+3)(y-1) | | 2(y+4)+3(y+3)= | | (2x+3)+(4x+2)=29 | | 8y=96x-40 | | x+4x-x-4+x+5x+3x+15=x+5x+x+4 | | x^2-12x-14=0 |

Equations solver categories